2017
DOI: 10.1007/s00421-017-3654-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of constant torque and constant angle stretching on the muscle and tendon tissue properties

Abstract: PurposeStatic stretching induces acute structural changes of the muscle–tendon unit (MTU) that are related to the intensity or duration of stretching. It has been reported that stretching with a constant torque (CT) leads to greater joint range of motion changes than stretching with a constant angle (CA). Whether or not this difference is due to different structural changes of the MTUs of the lower leg and ankle plantar flexors is not known. Therefore, the purpose of this study was to compare the acute effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
40
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 26 publications
13
40
2
1
Order By: Relevance
“…PRT was not changed at any time point after the single static stretching exercise. This is in accordance with some other studies (Magnusson, Aagard, Simonsen, & Bojsen-Møller 1998), but not all the previous studies dealing with similar (Kay et al, 2015;Opplert et al, 2016) or higher durations of stretching (Kay & Blazevich, 2009;Konrad et al, 2017a;2017b;2019;Konrad & Tilp, 2020;Nakamura, Ikezoe, Takeno, & Ichihashi, 2013;Opplert et al, 2016). The controversial results of Kay et al (2015), who also considered 1 min of total stretching, might be explained by the different stretching approaches.…”
Section: Statistical Analysessupporting
confidence: 91%
See 4 more Smart Citations
“…PRT was not changed at any time point after the single static stretching exercise. This is in accordance with some other studies (Magnusson, Aagard, Simonsen, & Bojsen-Møller 1998), but not all the previous studies dealing with similar (Kay et al, 2015;Opplert et al, 2016) or higher durations of stretching (Kay & Blazevich, 2009;Konrad et al, 2017a;2017b;2019;Konrad & Tilp, 2020;Nakamura, Ikezoe, Takeno, & Ichihashi, 2013;Opplert et al, 2016). The controversial results of Kay et al (2015), who also considered 1 min of total stretching, might be explained by the different stretching approaches.…”
Section: Statistical Analysessupporting
confidence: 91%
“…#= significant difference in analysis of variance, * = significant difference to pre-value data, mean ±SD. (Herda, Cramer, Ryan, McHugh, & Stout, 2008;Marek et al, 2005;Konrad et al, 2019) have reported a decrease in maximum strength performance following a single static stretching exercise, the results of others and the current study suggest that the maximum performance is not negatively affected (Konrad et al, 2017a;Konrad & Tilp, 2020;Kubo et al, 2001;Zakas, Doganis, Papakonstandinou, Sentelidis, & Vamvakoudis, 2006). These controversial results could possibly be explained by the differences in overall stretch duration, as summarized in the reviews by Kay and Blazevich (2012) and Behm et al (2016), who pointed out that only stretching for 60 s or longer can induce a detrimental effect on maximum performance.…”
Section: Statistical Analysessupporting
confidence: 66%
See 3 more Smart Citations